Competencia y circulación de las elites económicas: teoría y aplicación al caso del Perú - Figueroa, Adolfo (2004)
This study aims at understanding the behavior of economic elites in the Third World.Because economic elites concentrate the property of physical capital in society, theiractions influence the living conditions of the masses. The literature on the elite's behavioris, however, very limited. This study is an attempt to take some steps to fill this gap.The behavior that is emphasized is the investment in social capital. A theory of socialnetworks is thus proposed. A prediction of the theory is that the accumulation of socialcapital depends on the same set of factors that explain the accumulation of physicalcapital. Therefore, the economic elites do not circulate endogenously. The case of Peruis examined in the light of this theory. The results show consistency with the predictionsof the theory. The conclusion of this study is not in accord with the usual optimism laiddown on social capital as the instrument for economic development of the masses.